TOGETHER WITH SMILES : SPREADING HAPPINESS AND BUILDING CHARACTER AT MUHAMMADIYAH ORPHANAGE SIMOKERTO LKSA BUYA HAMKA - Imtihanatul Ma’isyatuts Tsalitsah; Muhammad Wahid Nur Tualeka; Maheswari Ayu Pratiwi; Fani Maulina (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Muhammadiyah Orphanage Simokerto LKSA BUYA HAMKA, located in Surabaya, has 30 children from diverse backgrounds, ranging from early childhood education to elementary school. Children face various challenges in their community, which are addressed by their parents. Many cannot express their emotions and their needs are not met. Through workshops, children can communicate with each other. To improve the Global Health Environment, creative education and learning must be provided to children so that they understand their environment and help them make the best use of it. This study aims to understand the effectiveness of seminars and workshops with the theme "Together with a Smile: Spreading Happiness and Building Character" and its impact on children and the environment. The PjBL (Project Based Learning) program aims to enhance their life experiences, reduce plastic usage, teach them about various aspects of happiness, food, and educate them to be kind and considerate.